2003
DOI: 10.1139/g02-099
|View full text |Cite
|
Sign up to set email alerts
|

A molecular marker map in 'Kanota' × 'Ogle' hexaploid oat (Avenaspp.) enhanced by additional markers and a robust framework

Abstract: Molecular mapping of cultivated oats was conducted to update the previous reference map constructed using a recombinant inbred (RI) population derived from Avena byzantina C. Koch cv. Kanota x Avena sativa L. cv. Ogle. In the current work, 607 new markers were scored, many on a larger set of RI lines (133 vs. 71) than previously reported. A robust, updated framework map was developed to resolve linkage associations among 286 markers. The remaining 880 markers were placed individually within the most likely fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
146
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(156 citation statements)
references
References 53 publications
(66 reference statements)
10
146
0
Order By: Relevance
“…K Pellizzaro et al population encompassed a total genetic distance of 1,397.5 cM (Figure 1). These results are in agreement with the results of molecular mapping previously performed in hexaploid oats (O'Donoughue et al 1995, Wight et al 2003, Zhu and Kaeppler 2003, Tinker et al 2009). The expected number of linkage groups is 21, corresponding to the number of chromosomes in each haploid cell (n) of hexaploid oat.…”
Section: Resultssupporting
confidence: 92%
“…K Pellizzaro et al population encompassed a total genetic distance of 1,397.5 cM (Figure 1). These results are in agreement with the results of molecular mapping previously performed in hexaploid oats (O'Donoughue et al 1995, Wight et al 2003, Zhu and Kaeppler 2003, Tinker et al 2009). The expected number of linkage groups is 21, corresponding to the number of chromosomes in each haploid cell (n) of hexaploid oat.…”
Section: Resultssupporting
confidence: 92%
“…This yielded 19 linkage blocks spanning 640 cM. Since A. barbata has 14 chromosome pairs and likely 1600 cM ( Jin et al 2000;Wight et al 2003), our map is clearly a partial map. However, additional AFLP and RAPD loci have so far failed to extend the map coverage (M. Morine, unpublished data).…”
Section: Methodsmentioning
confidence: 91%
“…Newell et al (2011) explored genome-wide LD in oat and showed that to attain values of r 2 = 0.2 between markers, one marker per centi-Morgan (cM) was needed. The most comprehensive oat map available, 'Kanota' 9 'Ogle,' is 1,890 cM (Wight et al 2003); thus, approximately 2,000 markers would be required to reach an average LD between markers and causal alleles of 0.2. Recent advances in Diversity Array Technology (DArT) markers in oat and current single nucleotide polymorphism (SNP) development can provide such density requirements for oat.…”
Section: Introductionmentioning
confidence: 99%